2011
DOI: 10.1007/s00432-011-1090-1
|View full text |Cite
|
Sign up to set email alerts
|

A C118T polymorphism of ERCC1 and response to cisplatin chemotherapy in patients with late-stage non-small cell lung cancer

Abstract: Our results suggest that this polymorphism of ERCC1 at codon 118 is associated with patient response to cisplatin-based chemotherapy in treatments of late-stage NSCLC. Moreover, by assaying this SNP in blood cells, the ERCC1 codon 118 may represent a valuable biomarker in developing individualized treatments for NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…The predictive value of ERCC1 expression in platinum-based chemotherapy responses has been reported in various cancers such as non-small cell cancer, ovarian cancer, and cervical cancer, as well as BC (Dabholkar et al, 1994;Kong et al, 2006;Bellmunt et al, 2007;Chen et al, 2010;Hoffmann et al, 2010;Okuda et al, 2011;Park et al, 2011;Cheng et al, 2012;Lv et al, 2014). A systemic review published in 2012 further confirmed the predictive value of ERCC codon C118T polymorphism in advanced colorectal patients treated with platinum-based chemotherapy in the Asian population.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The predictive value of ERCC1 expression in platinum-based chemotherapy responses has been reported in various cancers such as non-small cell cancer, ovarian cancer, and cervical cancer, as well as BC (Dabholkar et al, 1994;Kong et al, 2006;Bellmunt et al, 2007;Chen et al, 2010;Hoffmann et al, 2010;Okuda et al, 2011;Park et al, 2011;Cheng et al, 2012;Lv et al, 2014). A systemic review published in 2012 further confirmed the predictive value of ERCC codon C118T polymorphism in advanced colorectal patients treated with platinum-based chemotherapy in the Asian population.…”
Section: Discussionmentioning
confidence: 79%
“…Polymorphism in the ERCC1 genes could also affect its expression, which may influence the chemotherapy responses in various cancers. A study by Cheng et al (2012) reported that the C118T polymorphism of ERCC1 is associated with patient responses to cisplatin-based chemotherapy in late-stage non-small cell lung cancer. The response rate of patients carrying an ERCC1 codon 118 C/C allele was more than two-fold higher as compared with that of patients with either the C/T or T/T genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms have also been shown to be important. Patients with at least one C allele at codon 118 of the ERCC1 gene have a greater response to cisplatin treatment [98] and better overall survival [99] than those with a T allele. A phase II trial of 42 patients demonstrated significant improvements in overall response rates when NSCLC patients had their chemotherapy regime customised based on their genotype for two SNPs (118T/C and 8092C/A) in the ERCC1 gene and two in the ribonucleotide reductase M1 gene(À37C/A and À524T/C) [100].…”
Section: Excision Repair Cross-complimentary Group I (Ercc1)mentioning
confidence: 99%
“…Ren et al (2012) indicated that AAT codons of ERCC1 rs11615 might be a predictive marker for patients with non-small cell lung carcinoma (NSCLC) treated with platinum-based chemotherapy. Cheng et al (2012) found that the C allele of ERCC1 rs11615 polymorphism was associated with longer response to cisplatin-based chemotherapy in treatment of last-stage NSCLC than T allele. Gao et al (2014) found that the ERCC1 polymorphisms rs11615 and rs3212986 were negatively associated with response to chemotherapy and survival time of patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 92%
“…Multiple previous studies have reported that ERCC1 and ERCC2 were associated with the response to cisplatin-based chemotherapy and clinical outcome in several cancers (Kamikozuru et al, 2008;Park et al, 2011;Cheng et al, 2012;Ren et al, 2012;Chen et al, 2013;Rumiato et al, 2013;Gao et al, 2014;Li et al, 2014b). Park et al (2011) reported that the ERCC1 rs3212986 polymorphism was correlated with treatment outcome of metastatic gastric cancer treated with cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%